Time in the philosophy of Gabriel Marcel - Tattam, Helen (2011)
This thesis aims to determine what is distinctive to the philosophy of Gabriel Marcel (1889-1973). While his work has largely been received as a form of 'Christian existentialism' (notably by Jean-Paul Sartre), and thus interpreted in relation to other philosophies of existence, it is my contention that this prevents an appreciation of his specificity. I therefore recommend a new reading of his thought, which, through analysis of his various philosophical presentations of time, re-situates him within the twentieth-century French intellectual tradition. Part I of the thesis provides an introduction to his philosophy of time, analysing his position in specific relation to Henri Bergson (1859-1941). Chapter One raises the question as to whether his position is then compromised by his engagement with eternity, for this seems to undermine time's significance. However, what begins to emerge from Chapter Two onward, is that such a question may be inappropriate with respect to Marcel's understanding of philosophy. Part II (Chapters Three and Four) then explores the implications that his work’s various modes have on the content of his arguments: first, the diary-form of his formative works and his (continuing) use of a first-person narrative style in his essays and lectures; and second, the (non-narrative) form of his theatre, to which Marcel also accorded philosophical significance. Here, Marcel is read alongside Paul Ricœur (1913-2005) and Emmanuel Lévinas (1906-1995), who also tried to approach philosophy differently – as is especially manifest in their conceptions of time. Finally, Part III (Chapter Five) reconsiders the relation between Marcel’s philosophy and religion, asking how his references to God affect the basis of his philosophy, and what this entails for interpreting time in his work. In light of these discussions, the conclusion then reflects on what philosophy is for Marcel, and how he should therefore be received.